Menelaah Humor Miftah Maulana terhadap Tukang Bakul Es Teh dari Perspektif Etika Dakwah - Hasyim, Muhammad (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This research is motivated by the controversy that arose due to the delivery of crude humor with a derogatory tone by the famous preacher Miftah Maulana Habiburrahman to Mr. Sunhaji, which drew widespread criticism from the public. This phenomenon is interesting to study from the perspective of Islamic preaching ethics, especially from the perspective of Indonesian cleric and intellectual, Quraish Shihab. The study aims to investigate how ethics and preaching strategies should be applied in delivering religious messages, as well as how interactions between preachers and audiences can influence public perception of the image of Islam. The method used is descriptive qualitative research with a case study approach, focusing on the analysis of controversial preaching events. The results show that ideally preaching should be delivered wisely, with noble morals, inclusively, without offending certain parties, and with patience. In conclusion, the use of humor in preaching must remain within the corridor of ethics, respect human dignity, and reflect the values of Islam which are rahmatan lil 'alamin. Therefore, preachers need to be more careful in choosing a communication style so that the preaching message does not actually cause resistance or misunderstanding in society